Randomized clinical trial to evaluate the effect of fecal microbiota transplant for initial Clostridium difficile infection in intestinal microbiome - Green, John; Camacho Ortiz, Adrián; Gutiérrez Delgado, Eva María; García Mazcorro, José Francisco; Mendoza Olazarán, Soraya Sarahí; Martíne Meléndez, Adrián; Palau Davila, Laura; Baines, Simon D.; Maldonado Garza, Héctor Jesús; Garza González, Elvira (Public Library of Science, 2017)
Objective The aim of this study was to evaluate the impact of fecal donor-unrelated donor mix (FMTFURM) transplantation as first-line therapy for C. difficile infection (CDI) in intestinal microbiome. Methods We designed an open, two-arm pilot study with oral vancomycin (250mg every 6 h for 10–14 days) or FMT-FURM as treatments for the first CDI episode in hospitalized adult patients in Hospital Universitario “Dr. Jose Eleuterio Gonzalez”. Patients were randomized by a closed envelope method in a 1: 1 ratio to either oral vancomycin or FMT-FURM. CDI resolution was considered when there was a reduction on the Bristol scale of at least 2 points, a reduction of at least 50% in the number of bowel movements, absence of fever, and resolution of abdominal pain (at least two criteria). From each patient, a fecal sample was obtained at days 0, 3, and 7 after treatment. Specimens were cultured to isolate C. difficile, and isolates were characterized by PCR. Susceptibility testing of isolates was performed using the agar dilution method. Fecal samples and FMT-FURM were analyzed by 16S rRNA sequencing. Results We included 19 patients; 10 in the vancomycin arm and 9 in the FMT-FURM arm. However, one of the patients in the vancomycin arm and two patients in the FMT-FURM arm were eliminated. Symptoms resolved in 8/9 patients (88.9%) in the vancomycin group, while symptoms resolved in 4/7 patients (57.1%) after the first FMT-FURM dose (P = 0.26) and in 5/7 patients (71.4%) after the second dose (P = 0.55). During the study, no adverse effects attributable to FMT-FURM were observed in patients. Twelve isolates were recovered, most isolates carried tcdB, tcdA, cdtA, and cdtB, with an 18-bp deletion in tcdC. All isolates were resistant to ciprofloxacin and moxifloxacin but susceptible to metronidazole, linezolid, fidaxomicin, and tetracycline. In the FMT-FURM group, the bacterial composition was dominated by Firmicutes, Bacteroidetes, and Proteobacteria at all-time points and the microbiota were remarkably stable over time. The vancomycin group showed a very different pattern of the microbial composition when comparing to the FMT-FURM group over time. Conclusion The results of this preliminary study showed that FMT-FURM for initial CDI is associated with specific bacterial communities that do not resemble the donors’ sample.